The role of robotics in colorectal surgery. (12th February 2018) - Cheng, Christina L; Rezac, Craig
Abstract: Studies of laparoscopic approaches in colorectal surgery support the use of such methods. Compared with the open approach, laparoscopy reduces rates of postoperative complications and decreases length of stay, while providing equivalent oncologic outcomes. Nevertheless, much of colorectal surgery is still being performed by the open approach. This may be partly due to the technical challenges in performing laparoscopy, particularly when working in narrow spaces such as the pelvis. Moreover, some of the current literature has questioned the oncologic outcomes after laparoscopic surgery for rectal cancer. Robotic surgery has been heralded as the minimally invasive tool that can overcome these challenges. It has the advantages that it provides a three dimensional image, uses wristed instruments, and has a computer interface that allows for fluid and accurate movements. Overall, current evidence suggests that robotics is safe and feasible in colorectal surgery, and that short term and long term outcomes are comparable to those seen for laparoscopic approaches. Studies on the costs of robotic surgery show conflicting results, and this is arguably one of the biggest disadvantages of its use. Because robotic surgery is a relatively new technology, few large high quality studies are available. Most of the published studies in this area consist of retrospective reviews, case matched studies, and national database reviews. Large randomized prospective studies are needed to further support its use.